Difficulties in classifying categories of intellectual disability and the effect of sports physical activity on these categories - amroune, mafteh; ben yamina, Said; kaja, ridha (sports creativity, 2025)
Before talking about this category of children, it is necessary to point out an important point, which is the starting point of the study in dealing with this category through research, as what distinguishes the above researches is only a few of them, which dealt with the category of the mentally retarded, or other categories of disability, we notice that emotional or emotional charge by the researchers, which makes the research lose its value. Also, this type of emotionally charged research does not provide any service to this category. Therefore, the logic was to deal with this category within the framework of complete objectivity, without excessive emotional charge, and to deal with it within the framework of its characteristics, and this is the most appropriate, because the mentally retarded person does not need to be treated with pity, as much as he needs to be treated within the framework of his particularities. And that what we do to them, out of duty, whether through our scientific research or through our work with them, because they need it most, and according to C. Alain, those who do not know are rare, either because they do not want to know, or because they are helpless, here we find the real dilemma, known as a time when the child was directly neglected when he misinterpreted the triangle once or twice. Reasonable behavior.